MAXIMISING THE ECONOMIC BENEFITS OF GREEN RETROFITTING OF EXISTING BUILDINGS IN MALAYSIA - Zahari, Aini Najwa Mohd; Keng, Tan Chin (Journal of Architecture, Planning and Construction Management, 2025)
There are two future predictions based on current trends: the style of working remotely and the growth of demand for tiny houses. However, the trends are cross-conflict due to the limited space in tiny houses for working activities. One of the most significant influences on working productivity is the suitability of furniture design for working activity. One of the observation results in the furniture design market shows that the available furniture design for working activities is usually not designed for home space. This paper studies the possible types of furniture design for working space in tiny houses. Thematic Analysis extracted from design discussions with 15 Key Informant Interviews (KII) specialises in design (Industrial Design, Entrepreneur, Interior Designer, and Architect) from Malaysia. Results show the attributes of workspace furniture design for tiny houses, such as the consideration ratio of working surface and the longevity time usage for working remotely from the tiny house. These attributes are helpful for future research and development of the furniture design process, specifically in designing furniture design for workspaces in tiny houses. The consistency statement by KII leads to ordering the evaluation of furniture design criteria for workspace in tiny houses. Most of KII is concerned about the technical part, followed by functionality, concept aesthetics, and cost. The perceptual positioning map of workspace furniture shows the working furniture for remote working and their positioning, indicating a space function relationship. The presentation of furniture mapping relates to the estimation for designing furniture for workspaces in tiny houses in the future.